Challenges in Treating Syphilis in Rural Areas : A Comprehensive Systematic Review - Reza Agustiantwo Putra; Fenny (International Medical Journal Corp. Ltd, 2026)
Introduction: Syphilis, a curable sexually transmitted infection, continues to cause substantial morbidity, including congenital syphilis (CS), due to treatment failures. Rural areas face unique, compounded barriers. This review synthesizes evidence on challenges and solutions for syphilis treatment in rural settings. Methods: A systematic review of 80 peer-reviewed studies (2000–2026) from databases including PubMed, Cochrane, and global health sources. Inclusion criteria: rural/remote settings, focus on syphilis treatment barriers (not just screening), any study design with ≥10 participants, and specific syphilis outcomes. Data extraction covered diagnostic delays, treatment access, system barriers, patient factors, and interventions. Results: Key findings: (1) Diagnostic delays: Offsite testing in rural South Africa caused median 34-day treatment delays [1]; onsite immunochromatographic strip (ICS) testing achieved 89.4% correct diagnosis/treatment vs. 60.8% offsite [2]. (2) Treatment access: Benzathine penicillin G (BPG) shortages affected 41% of countries, causing referral delays and alternative suboptimal treatments [3]. (3) Healthcare system failures: Inadequate prenatal care contributed to 23–47% of CS cases [6,7]; only 64.8% of pregnant women completed all three BPG doses [1]. (4) Social determinants: Housing instability (OR 3.42) and substance use (42% of CS cases) were strongly associated with CS [7]. (5) Interventions: Point-of-care (POC) testing reduced treatment delays by 16 days [17] and improved treatment rates from 51.1% to 95.2% [12]; conditional cash transfers increased treatment completion from 45% to 78% [5]; alternative antibiotics (ceftriaxone, doxycycline) showed high efficacy but resistance limits azithromycin [54]. Discussion: Rural syphilis treatment failures arise from interlocking barriers: geographic isolation, laboratory dependency, BPG supply chain fragility, inadequate prenatal care, and social vulnerabilities. Successful interventions address multiple levels simultaneously: POC testing + immediate treatment + financial support + partner services. Alternative regimens are promising but not first-line in pregnancy. Conclusion: Eliminating CS in rural areas requires integrated, multilevel strategies: universal POC testing with same-day treatment, strengthened BPG supply chains, conditional cash transfers, and addressing social determinants (housing, substance use). Policy changes allowing non-physicians to treat syphilis and decentralization of services are critical.